(untitled) (International Journal of Physiotherapy, 2023)
Aims: Exploring the applicability and intensity of exergaming for children with cancer is essential. This study aimed to examine the applicability of Nintendo WiiTM exergames and determine the intensity of Physical Activity (PA) provided by these exergames for children with acute lymphoblastic leukemia. Methods: In this preliminary study, 31 children aged 6-14 years of both sexes were asked to play Wii exergames for a 60-minute research session. Using the Arabic video game applicability questionnaire, the children were instructedto score seven statements regarding usability, engagement, and enjoyment of exergames. In addition, heart rate (HR), predicted heart rate maximum (pred. HRmax), rating of perceived exertion (RPE), and oxygen saturation (SpO2) were measured at baseline and every 15 min during the session. Results: About 74.2%, 83.9%, and 93.6% of the children agreed that the games were usable, engaging, and enjoyable, respectively. Exergames were of moderate intensity as the children reached 59.22±8.40 % of age-predicted HRmax: the HR and its percentage of increase from the pred. HRmax (% pred. HRmax) was significantly higher in girls than in boys (P=0.01). The level of perceived exertion was moderate (5.74± 0.63). Conclusion: Implementation of Nintendo Wii exergames for 60 minutes was found to be applicable. In addition, it resulted in PA of moderate intensity.